Penggunaan Model Pembelajaran Kontekstual Untuk Meningkatkan Kemampuan Komunikasi Matematis Siswa Sekolah Dasar - Erwin Eka Saputra (Prodi PGSD Unsultra, 2022)
This study aims to determine: (1) the improvement of mathematical communication skills through the contextual teaching model, (2) the improvement of mathematical communication skills through the conventional teaching model, and (3) the comparison between the two models to determine which is more effective. This research is a quasi-experimental study. The experimental class used a contextual teaching model, while the control class used a conventional teaching model. The research sample consisted of sixth-grade students from two schools: 15 students from SDN 1 Moramo and 17 students from SDN 11 Moramo. The results showed that: (1) based on the average pretest and posttest scores of the experimental class, the contextual teaching model led to an improvement in students’ mathematical communication skills; (2) based on the average pretest and posttest scores of the control class, there was also a significant improvement in students’ mathematical communication skills through the conventional model; and (3) the average N-Gain score for the experimental class was 0.6364, categorized as moderate, while the average N-Gain score for the control class was 0.2229, categorized as low. Therefore, the improvement in mathematical communication skills in the experimental class was better than that of the control class.